2018
DOI: 10.1016/j.jamda.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Based Interventions to Improve Mobility: A Systematic Review and Meta-analysis

Abstract: This meta-analysis provides support for the fact that cognitive training interventions can improve mobility-related outcomes, especially during challenging walking conditions requiring higher-order executive functions. Additional evidence from well-designed large-scale randomized clinical trials is warranted to confirm the observed effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 39 publications
3
63
0
3
Order By: Relevance
“…A single‐blind randomized controlled trial with 5 years of follow‐up showed that reasoning training (a type of cognitive training) could slow functional decline in self‐reported instrumental activities of daily life . A meta‐analysis showed that cognitive training interventions could improve function‐related outcomes, especially physical function requiring higher‐order executive functions . The mechanisms underlying the relationship between cognitive function and functional limitation are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single‐blind randomized controlled trial with 5 years of follow‐up showed that reasoning training (a type of cognitive training) could slow functional decline in self‐reported instrumental activities of daily life . A meta‐analysis showed that cognitive training interventions could improve function‐related outcomes, especially physical function requiring higher‐order executive functions . The mechanisms underlying the relationship between cognitive function and functional limitation are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…42 A meta-analysis showed that cognitive training interventions could improve function-related outcomes, especially physical function requiring higher-order executive functions. 43 The mechanisms underlying the relationship between cognitive function and functional limitation are not clear. At the simplest level, execution of the physical task involves the sensorimotor nervous system and requires information processing and attention.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 ) Pilot intervention trials to enhance EF either by cognitive training or brain stimulation have shown improvements in gait velocity. 16 , 17 )…”
Section: Gait Speed and Cognitive Decline In Generalmentioning
confidence: 99%
“…Alternatively, these individuals could be included in interventions with the aim of FRIENDSHIPS AND LONELINESS IN OLDER ADULTS 29 improving the other contributing factors to loneliness and psychological well-being such as health status and mobility (Theeke, 2009). These could include cognitive based interventions to improve mobility (Marusic, Verghese, & Mahoney, 2018) and physical activity interventions to improve mobility (Yeom, Keller, & Fleury, 2009) and health status (Hwang & Braun, 2015). As well as directly targeting psychological well-being with the aim of reducing loneliness in tandem.…”
Section: Discussionmentioning
confidence: 99%